SMALLHOLDERS' AND COOPERATIVES' READINESS ANALYSIS IN OIL PALM SMALLHOLDERS' PLANTATION REPLANTING PROGRAM (Case Study of Farmers in Ophir, West Pasaman Regency, West Sumatra Province) - Amalia, Rizki; Nurkhoiry, Ratnawati; Nasution, Zulfi Prima Sani; Kurniawan, Ambar (Jurnal Penelitian Kelapa Sawit, 2017)
The study of replanting models for smallholding oil palm plantation analysis is focus on smallholders and cooperatives' readiness assessment involves in replanting and business development program. The research objects are four oil palm plantantion cooperatives (KPS) in Ophir, West Pasam: KPS Perintis, KPS Indah, KPS Maju and KPS Makmur. Smallholders readiness in replanting and business development program was assessed through three criterias, which are ability to repay of debt, good faith to join community, and cooperative capacity. The results showed that smallholders in KPS Ophir are basically ready and feasible in obtaining financing and follow the oil palm replanting program, but access to financing and regulations that requires avalis become constrains for the smallholders.